Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pasien Pre Operasi - Lidya Lumbantoruan; Lannasari Lannasari; Solehudin Solehudin (Institut Nalanda, 2024)
Introduction Anxiety is a common phenomenon in hospital patients, especially those about to undergo surgery. The patient's mental preparation before surgery needs to be considered because anxiety will affect the procedure and the diagnosis made. Family involvement and support will help prepare the patient mentally and create the patient's enthusiasm to continue treatment. The aim is to determine the level of support and anxiety of pre-operative patients before surgery at Tebet Hospital in 2023. The research method used in this research is a quantitative correlation method with a cross-sectional approach and total sampling technique. The sample for this research consisted of 44 respondents. The results of the study showed that there was a relationship between family support and the anxiety level of pre-operative patients at Tebet Hospital. Bivariate analysis using the chi-square test obtained a p value of 0.017. Conclusions and Suggestions Family support is needed to support the patient's mental preparation and be able to provide encouragement to the patient. Suggestions for future researchers are to explore further whether patient anxiety levels occur more frequently during major or minor operations than pre-operative operations.